A Score to differentiate Takotsubo syndrome from non-ST-elevation myocardial nfarction in women at the bedside. Issue 1 (11th March 2020) - Looi, Jen-Li; Poppe, Katrina; Lee, Mildred; Gilmore, Jill; Webster, Mark; To, Andrew; Kerr, Andrew J
Abstract : Objective: A score to distinguish Takotsubo syndrome (TS) from acute coronary syndrome would be useful to facilitate appropriate patient investigation and management. This study sought to derive and validate a simple score using demographic, clinical and ECG data to distinguish women with non-ST elevation myocardial infarction (NSTEMI) from NSTE-TS. Methods: The derivation cohort consisted of women with NSTE-TS (n=100) and NSTEMI (n=100). Logistic regression was used to derive the score using ECG values available on the postacute ward round on day 1 post-hospital admission. The score was then temporally validated in subsequent consecutive patients with NSTE-TS (n=40) and NSTEMI (n=70). Results: The five variables in the score and their relative weights were: T-wave inversion in ≥6 leads (+3), recent stress (+2), diabetes (−1), prior cardiovascular disease (−2) and ST-depression in any lead (−3). When calculated using ECG values obtained at admission, discrimination between conditions was very good (area under the curve (AUC) 0.87 95% CI 0.83 to 0.92). The optimal score cut-point of ≥1 to predict NSTE-TS had 73% sensitivity and 90% specificity. When applied to the validation cohort at admission, AUC was 0.82 (95% CI 0.75 to 0.90) and positive and negative predictive values were 78% and 81%, respectively. On day 1 post-admission, AUC was 0.92 (95% CI 0.87 to 0.97), with positive and negative predictive values of 77% and 91%, respectively. Conclusion: This NSTE-TS score is easy to use and may prove useful in clinical practice to distinguish women with NSTE-TS from NSTEMI. Further validation in external cohorts is needed.